Authentic Assessment of Affective Domain in Islamic Education and Character BuildingÂ at A Curriculum 2013 Pilot Project Elementary SchoolÂ in Banyumas Regency Central Java Indonesia - Rohmad, Rohmad (International Conference of Moslem Society, 2019)
Authentic assessment in the 2013 curriculum requires each teacher to conduct performs a fairly complex assessment of spiritual and social attitudes, knowledge, and skills. The problem in this research is how authentic assessment of affective domain in Islamic Education and character-building is implemented in a curriculum 2013 pilot project elementary school in Banyumas Regency Central Java Indonesia. This research is field research classified as descriptive qualitative research. The interview and observation methods were used to collect the data of the process of authentic assessment of affective domain in the subjects of Islamic and character Education. The documentation method was used to gain the data related to the school profiles and planning documents, implementation and assessment processing. The analysis technique chosen in this research was descriptive analysis technique using inductive and deductive thinking methods and following Miles and Huberman model of data analysis. The study found that the implementation of an authentic assessment in the school was carried out both manually and automatically using application through the process of 1) planning done by determining the character to be measured and making an assessment format referring to KI-1 and KI-2 , 2) implementation of the assessment carried out by observing and recording the attitudes of the participants, 3) value processing done collaboratively between the Islamic and Character Education teachers (PAI and BP) with the Class Teacher then recapitulating the attitude values and making the description, and 4) Follow-up carried out by PAI & BP Teachers and Class Teachers by providing rewards, motivation, coaching, habituation programs, and mentoring.